Germination, emergence, and dormancy of Mimosa pudica - Chauhan, Bhagirath S.; Johnson, David E. (Wiley, 2009)
Mimosa pudica (common sensitive plant) is a problematic weed in many crops in tropical countries. Eight experiments were conducted to determine the effects of light, seed scarification, temperature, salt and osmotic stress, pH, burial depth, and rice residue on the germination, seedling emergence, and dormancy of M. pudica seeds. Scarification released the seeds from dormancy and stimulated germination, though the germination of the scarified seeds was not influenced by light. The scarification results indicate that a hard seed coat is the primary mechanism that restricts germination. The germination increased markedly with the exposure to high temperature “pretreatment” (e.g. 150°C), which was achieved by placing non‐scarified seeds in an oven for 5 min followed by incubation at 35/25°C day/night temperatures for 14 days. The germination of the scarified seeds was tolerant of salt and osmotic stress, as some seeds germinated even at 250 mmol L−1 NaCl (23%) and at an osmotic potential of −0.8 MPa (5%). The germination of the scarified seeds was >74% over a pH range of 5–10. The seedling emergence of the scarified seeds was 73–88% at depths of 0–2 cm and it gradually decreased with an increasing depth, with no seedling emergence at the 8 cm depth. The rice residue applied to the soil surface at rates of ≤6 t ha−1 did not influence the seedling emergence and dry weight. The information gained from this study identifies some of the factors that facilitate M. pudica becoming a widespread weed in the humid tropics and might help in developing components of integrated weed management practises to control this weed.